The Health Halo Trend in UK Television Food Advertising Viewed by Children: The Rise of Implicit and Explicit Health Messaging in the Promotion of Unhealthy Foods - Whalen, Rosa (Int J Environ Res Public Health, 2018)
Monitoring the creative content within food marketing to children is strongly advocated by public health authorities, but few studies address the prevalence of health-related messaging in television adverts. Food and beverage adverts (n = 18,888 in 2008, n = 6664 in 2010) from UK television channels popular with children were coded and analyzed. Physical-activity depiction displayed an 18.8 percentage point increase from 2008 (4.4%) to 2010 (23.2%). Of the food adverts containing physical-activity depiction in 2010, 81.1% were for non-core foods. The appearance of health claims in food adverts in 2010 increased 4.1 percentage points from 2008 levels (20.7% to 24.8%) where the majority of food adverts featuring health and nutrition claims were for non-core foods (58.3%). Health-related (e.g., health/nutrition, weight loss/diet) appeals were used in 17.1% of food adverts during peak child-viewing times, rising to 33.0% of adverts shown on dedicated children’s channels in 2010. Implicit (physical activity) and explicit (health claims) health messages are increasingly prevalent in UK television food advertising viewed by children, and are frequently used to promote unhealthy foods. Policy makers in the UK should consider amendments to the existing statutory approach in order to address this issue.